Political Instability Causes & Affects - Rashid, Zarina; Rashid, Shahir (Pakistan Journal of Humanities and Social Sciences, 2024)
This article investigates the relationship between political instability and economic growth. We define “political instability” as the propensity of a government collapse, and we argues in which political instability and economic growth are interdependent to each other. The main result of this article is that in countries and as well as in Pakistan time periods with a high propensity of government collapse, growth is significantly lower as otherwise. This effect remains strong and shows consequences of political instability to socio-economic policies, unequal distribution of wealth, corruption, unemployment, poverty, mental and physical health, internal external terrorism and poor family leadership.” This article explores the complex link between political instability and economic growth, emphasizing the definition of "political instability" as the propensity for the dissolution of the government. The central theme of our argument is the relationship between economic expansion and political instability. This study's main conclusion is that, in nations—Pakistan being one prominent example eras marked by a higher risk of political collapse tend to have far slower rates of economic growth than periods marked by greater stability. This research reveals the profound effects of political instability on socio-economic policies, highlighting its long-lasting influence. The consequences are multifaceted, including uneven economic distribution, widespread corruption, prolonged joblessness, high rates of poverty, and negative impacts on mental and physical health. Moreover, political unrest has a significant impact on the incidence of both domestic and foreign terrorism, making security issues worse in impacted areas. Additionally, the study clarifies how political instability undermines the authority of families and shatters the foundation of social systems. This paper offers a thorough examination of the complex effects of political instability, shedding light on how it affects numerous socioeconomic indicators and economic growth. Comprehending these processes is of paramount importance for policymakers, scholars, and international leaders who aim to tackle the obstacles presented by political instability and promote stable, robust communities.